2011
DOI: 10.3846/13928619.2011.560639
|View full text |Cite
|
Sign up to set email alerts
|

Motor Biofuel-Powered CHP Plants—a Step Towards Sustainable Development of Rural Lithuania

Abstract: This paper focuses on the benefits that can be attained from the correct option of smallscale combined heat and power plant (CHP) relative to fuel availability and sphere of application. The analysis serves as a means of highlighting some of the owners of large-scale farms as well as holders of industrial greenhouses that influence the penetration of small-scale cogeneration plants running on bio-based liquid fuels. The identification of the main influencing factors and their weight is the first step towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…NOx emission using B100 was observed in comparison to B0 when used at 100 load. These results were supported by studies on BDF combustion: approximately 11.6 increase of NOx emission from BDF B100 was observed when compared to those from petro-diesel B0 26 , and the NOx emissions increased proportionally to fuel oxygen mass 23 . It has been shown that the increase in NOx emissions is a signal of higher heat release and may be explained by the cetane number as well as relate to the oxygen molecules present in the compound 27 .…”
Section: Gaseous Emissions From Diesel Engine Combustion Of Candlenutsupporting
confidence: 58%
See 2 more Smart Citations
“…NOx emission using B100 was observed in comparison to B0 when used at 100 load. These results were supported by studies on BDF combustion: approximately 11.6 increase of NOx emission from BDF B100 was observed when compared to those from petro-diesel B0 26 , and the NOx emissions increased proportionally to fuel oxygen mass 23 . It has been shown that the increase in NOx emissions is a signal of higher heat release and may be explained by the cetane number as well as relate to the oxygen molecules present in the compound 27 .…”
Section: Gaseous Emissions From Diesel Engine Combustion Of Candlenutsupporting
confidence: 58%
“…By increasing the engine load, the fuel undergoes complete combustion in the engine cylinder because of increased availability of oxygen or air supply which reduces CO emission and increases engine temperature. The inverse proportion of CO emission to the percentage of BDF blends can be attributed to fuel oxygen mass as suggested by Raslavičius et al 23 .…”
Section: Gaseous Emissions From Diesel Engine Combustion Of Candlenutmentioning
confidence: 81%
See 1 more Smart Citation
“…These tendencies were observed and verified during the experiments made by Raslavičius and Strakšas [26] on a four cycled tractor diesel engine D144 type with a biodiesel obtained from rapeseed oil. They obtained a level of NO x emissions for all the tested biofuels (B100 and RO) or compounded blends (B50/dB50) of average 5.1% to 12.2% higher than those of diesel fuel.…”
Section: Interdisciplinary Research In Engineering: Steps Towards Brementioning
confidence: 99%
“…This explains the fact that the rapeseed oil, having a percentage of oxygen (~ 10%) has smaller hydrocarbons emissions, for most of the functioning regimes relative to the diesel fuel, which does not contain oxygen. The high content of peroxides in the rapeseed oil has also a positive influence on the formation of hydrocarbons emissions [26]. Usually, the HC emissions for all biofules show tendencies towards decrease for most engine loads at different engine speeds in comparison with the diesel fuel.…”
Section: Interdisciplinary Research In Engineering: Steps Towards Brementioning
confidence: 99%